Associations of dietary insulin load and dietary insulin index with diabetic nephropathy and reduced kidney function among women: a case–control study - Faezeh Abaj; Atieh Mirzababaei; Mohammad Gholizadeh; Yasaman Aali; Paria Jadidi; Reza Amiri Khosroshahi; Cain C. T. Clark; Khadijeh Mirzaei (Journal of Health, Population and Nutrition)
Abstract Background Increased insulin levels lead to hyperinsulinemia and insulin resistance (IR). IR is one of the main causes of the onset and progression of Diabetic Nephropathy (DN) and kidney failure in type 2 diabetic patients. The present case–control study sought to investigate the relationship between dietary insulin load (DIL) and index (DII) and the odds of DN and kidney function decline. Methods At the Kowsar Diabetes Clinic in Semnan, Iran, we enrolled 105 eligible women with DN and 105 controls (30–65 years old). Dietary insulin load (DIL) and index (DII) were assessed using a 147-item food frequency questionnaire (FFQ). Using standard protocols, biochemical variables and anthropometric measurements were evaluated for all patients. To investigate potential associations, binary logistic regression was used. Results We found that higher DII was associated with 2.72 times higher odds of albuminuria (OR: 2.77; 95% CI 1.16, 6.63) and 1.92 times higher odds of DN (OR: 1.92; 95% CI 1.11, 3.32) compared to lower adherence. Additionally, DIL was found to be statistically highly connected with mild to severe reduction of glomerular filtration rate (GFR) in participants and 1.82 times greater odds of DN (OR = 1.82; 95% CI 1.01, 3.30). Conclusion The findings from this research showed that a higher odds of DN were related to a higher level of adherence to DIL and DII. Increased adherence to DIL was strongly correlated with the likelihood of a decreased GFR. To clarify our findings, more prospective research is necessary.